N-Terminal microdomain peptide from human dihydroorotate dehydrogenase: structure and model membrane interactions - Vicente, Eduardo F. [UNESP]; Nobre-Pavinatto, Thatyane M. [UNESP]; Pavinatto, Felippe J. [UNESP]; Oliveira Junior, Osvaldo Natale [UNESP]; Costa-filho, Antonio J. da [UNESP]; Cilli, Eduardo Maffud [UNESP] (Bentham Science Publishers, 2014)
The N-terminus of the human dihydroorotate dehydrogenase (HsDHODH) has been described as important for the enzyme attachment in the inner mitochondrial membrane and possibly to regulate enzymatic activity. In this study, we synthesized the peptide acetyl-GDERFYAEHLMPTLQGLLDPESAHRL AVRFTSLGamide, comprising the residues 33-66 of HsDHODH N-terminal conserved microdomain. Langmuir monolayers and circular dichroism (CD) were employed to investigate the interactions between the peptide and membrane model, as micelles and monolayers of the lipids phosphatidylcholine (PC), 3-phosphatidylethanolamine (PE) and cardiolipin (CL). These lipids represent the major constituents of inner mitochondrial membranes. According to CD data, the peptide adopted a random structure in water, whereas it acquired α-helical structures in the presence of micelles. The π–A isotherms and polarization- modulated infrared reflection-absorption spectroscopy on monolayers showed that the peptide interacted with all lipids, but in different ways. In DPPC monolayers, the peptide penetrated into the hydrophobic region. The strongest initial interaction occurred with DPPE, but the peptide was expelled from this monolayer at high surface pressures. In CL, the peptide could induce a partial dissolution of the monolayer, leading to shorter areas at the monolayer collapse. These results corroborate the literature, where the HsDHODH microdomain is anchored into the inner mitochondrial membrane. Moreover, the existence of distinct conformations and interactions with the different membrane lipids indicates that the access to the enzyme active site may be controlled not only by conformational changes occurring at the microdomain of the protein, but also by some lipid-protein synergetic mechanism, where the HsDHODH peptide would be able to recognize lipid domains in the membrane. - See more at: http://www.eurekaselect.com/122062/article#sthash.1ZZbc7E0.dpuf
Keywords: Circular dichroism; Human dihydroorotate dehydrogenase; Langmuir monolayers; peptide; Phospholipids; Polarization- modulated infrared reflection-absorption spectroscopy; Olid-phase peptide synthesis